2010
DOI: 10.1007/s00535-010-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for the development of cirrhosis in autoimmune hepatitis: Japanese NHO-AIH prospective study

Abstract: Autoimmune hepatitis (AIH) is a chronic and progressive liver disease characterized by histological interface hepatitis and circulating autoantibodies. Our aims were to evaluate risk factors that contribute to the outcome and, particularly, the development of liver cirrhosis in a prospective multicenter cohort study of AIH. One hundred and seventy-four patients were enrolled. Histologically 21 (12.1%) had cirrhosis at the initial observation and the remaining 153 showed chronic or acute hepatitis at presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…[3] However, some AIH patients develop liver cirrhosis and liver failure at initial presentation. [4,5] Hepatic inflammation is regulated by the activities of immune cells including lymphocytes, Kupffer cells, hepatocytes, and hepatic stellate cells. [6] Serum cytokines/chemokines are thought to be linked to the pathogenesis of AIH by activating these hepatic immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, some AIH patients develop liver cirrhosis and liver failure at initial presentation. [4,5] Hepatic inflammation is regulated by the activities of immune cells including lymphocytes, Kupffer cells, hepatocytes, and hepatic stellate cells. [6] Serum cytokines/chemokines are thought to be linked to the pathogenesis of AIH by activating these hepatic immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the age at the time of AIH diagnosis in the cirrhosis cases (60 years) was significantly higher than that in the non-cirrhosis cases. The period of onset for these cases is unknown; however, it has been reported that cirrhosis tends to develop in cases of onset at advanced ages (14). Miyake et al reported that the male-to-female ratio of cirrhosis cases is equal to that of non-cirrhosis cases of AIH (15); however, the male-to-female ratio of cirrhosis cases in the present study was 1:4.3, with the ratio of men being higher, although not significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis is sometimes complicated with AIH at diagnosis and influences its prognosis. AIH patients with cirrhosis had a worse survival 2 . The genetic and environmental factors are involved in the pathogenesis of AIH.…”
Section: Introductionmentioning
confidence: 94%